COMPARATIVE ANALYSIS OF DYNAMIC CHARACTERISTICS OF TURNSTILE AND FASTENING DEVICES, ROLLER, SKID, OR V-TYPES - Vasyliev, S. M. (Science and Transport Progress, 2008)
The mathematical model is developed for research of dynamic influences on the lengthy cargoes fixed with use of mobile fixing devices on basic cars, at various variants of impact of basic cars with other units of the rolling stock. Schedules of dependences of the maximal acceleration of a cargo from key parameters of fixing devices are obtained. Relationships, characteristic for dynamics of rolling, skidding and wedge fixing devices, are analyzed.